(untitled) (Economic Cooperation Organization Economic Journal, 2025)
The development of artificial intelligence technologies has a complex impact on the labor market. While it creates new opportunities and high-paying job fields for highly skilled workers, it also presents challenges such as the reduction of jobs and wage polarization for low-skilled workers. Robotics and automation are leading to job losses in sectors such as manufacturing, logistics, customer service, agriculture, law, healthcare, and journalism. At the same time, new professions such as data analysts and machine learning engineers are emerging.